Kejujuran Dalam Perspektif Hadis - Royansyah Royansyah; Mus’idul Milah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The motivation of this research is to find out about the importance of having an attitude of honesty in the study of hadith, so that the nature of dishonesty should not be used in muamalah in everyday life. Honesty is something that is highly prescribed in Islamic values, the value of honesty is a measure of one's faith, because the opposite of honesty is lying or deceit and that is something that has a value of deep dishonesty.This research method uses a qualitative approach with analysis and literature study. The results of this study include a general discussion of being honest both being honest according to the view of the Koran and hadith, being honest in carrying out assignments, being honest in trading and buying and selling, being honest with yourself or with others. The conclusion of this study shows that being honest is a must that must be owned by each individual person, as well as avoiding reasons for committing dishonesty, because being honest is a virtue and reflects one's faith. since early stage